Treatment of adults with acute uncomplicated malaria with azithromycin and chloroquine in India, Colombia, and Suriname - Kshirsagar, Nilima A (Res Rep Trop Med, 2017)
BACKGROUND: To explore the use of azithromycin–chloroquine (AZCQ) for the treatment of malaria, we conducted double-blind, randomized, non-inferiority studies in India, Colombia, and Suriname comparing the combination of azithromycin 1 g and chloroquine (CQ) 600 mg base once daily (QD) for 3 days versus atovaquone–proguanil (AP) or chloroquine plus sulfadoxine–pyrimethamine (SPCQ) in adults with acute uncomplicated Plasmodium falciparum malaria. METHODS: Patients were hospitalized until three documented negative blood smears and followed through Day 42. The primary end point was parasitologic cure at Day 28. RESULTS: In India, parasite clearance rates were 84% and 94% for AZCQ and SPCQ, respectively (95% confidence interval [CI] for the difference: −22.6, 0.8). In Colombia and Suriname, parasite clearance rates were 57% and 99% for AZCQ and AP, respectively (95% CI: −52, −32). A subsequent open-label, non-comparative third study using a 2 g dose of azithromycin and 600 mg of CQ in India and Colombia resulted in an overall efficacy rate of 97%. CONCLUSION: In India, Colombia, and Suriname, 1 g azithromycin with CQ QD for 3 days was inferior to established comparator agents. An improved response rate was observed when the dose of azithromycin was increased to 2 g.